Pathway to Demonstrating Clinical Efficacy of MIcrowave Breast Imaging: Qualitative and Quantitative Performance Assessment - O'Loughlin, Declan (My University, 2022)
n the last five years alone, there has been an increasing number of operational microwave breast imaging systems used in clinical trials, with increasingly large and diverse patient populations. However, despite this increased activity and volume of clinical evidence motivating research in the modality, large differences exist in how studies evaluate and report their findings. In this work, the qualitative and quantitative metrics used to measure both image quality and clinical effectiveness and efficacy are reviewed in detail. Image quality, effectiveness and efficacy do not have precise or agreed definitions and the differences between these definitions are discussed in detail. Finally, based on these understandings, the current evidence for clinical acceptance of microwave breast imaging is reviewed, with an emphasis on gaps in the trial populations to date.
PUBLISHED
Keywords: breast imaging; microwave imaging; performance evaluation; Next Generation Medical Devices